1998
DOI: 10.1046/j.1525-1497.1998.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving primary care residents’ proficiency in the diagnosis of skin cancer

Abstract: OBJECTIVE:To determine whether a brief, multicomponent intervention could improve the skin cancer diagnosis and evaluation planning performance of primary care residents to a level equivalent to that of dermatologists. PARTICIPANTS:Fifty-two primary care residents (26 in the control group and 26 in the intervention group) and 13 dermatologists completed a pretest and posttest. DESIGN:A randomized, controlled trial with pretest and posttest measurements of residents' ability to diagnose and make evaluation plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 18 publications
1
33
1
Order By: Relevance
“…11 This underscores the need for practical hands-on training and practice opportunities. Previous studies have described targeted educational interventions that have improved clinicians' ability to diagnose and plan evaluation strategies for cancerous skin lesions 12,13 and that have increased medical students' self-rated skill levels for cancer prevention and detection. 10 Teaching of the SCE seems to be suboptimal in the 7 medical schools studied, based on students' self-rated low skill levels.…”
Section: Commentmentioning
confidence: 99%
“…11 This underscores the need for practical hands-on training and practice opportunities. Previous studies have described targeted educational interventions that have improved clinicians' ability to diagnose and plan evaluation strategies for cancerous skin lesions 12,13 and that have increased medical students' self-rated skill levels for cancer prevention and detection. 10 Teaching of the SCE seems to be suboptimal in the 7 medical schools studied, based on students' self-rated low skill levels.…”
Section: Commentmentioning
confidence: 99%
“…The dermatology workforce is limited, and studies have found that PCPs can diagnose and appropriately refer melanoma at the same level as dermatologists if they receive targeted education. 8,9 Skin cancer training programs, both in person and web-based, have been shown to improve the knowledge and skills of PCPs, which is important because as few as 30% of primary care residents report receiving formal training in performing a skin examination. 6,8,10 -12 Few educational programs for skin cancer detection have been developed, and even fewer for practicing PCPs in particular.…”
mentioning
confidence: 99%
“…Physicians' overall triage error rate using the decision support software (13.3%) was similar to the triage error rate found for dermatologists in a recent study (15%). 5 Nineteen of 20 physicians made more correct triage decisions using the software than on their own, and physicians using the software averaged 3 more correct triage decisions than when they triaged on their own, representing a 20% improvement rate. Regarding cancerous lesions, primary care physicians' error rate using the decision support software (3.6%) was similar to that achieved by dermatologists in a previous study (0%).…”
Section: Discussionmentioning
confidence: 97%
“…Regarding cancerous lesions, primary care physicians' error rate using the decision support software (3.6%) was similar to that achieved by dermatologists in a previous study (0%). 5 In addition, unnecessary referrals and biopsies were reduced by half when physicians used the decision support software. These findings are especially encouraging given that 18 participants (90%) rated themselves between "somewhat" and "not at all" confident in their skin cancer triage skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation